2011
DOI: 10.1111/j.1528-1167.2011.03107.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet also benefits Dravet syndrome patients receiving stiripentol: A prospective pilot study

Abstract: SUMMARYWe aimed to test the efficacy of ketogenic diet (KD) in patients with Dravet syndrome (DS) not satisfactorily controlled by antiepileptic drugs (AEDs). We included prospectively 15 DS patients aged >3 years with partial response to AEDs including stiripentol. All patients had a seizure diary and clinical examination with Conners and Achenbach scales before KD, at 1 month following onset and every 3 months thereafter. At 1 month, 10 patients (66%) had a decrease of seizure frequency ‡75%. Efficacy was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 16 publications
0
59
0
Order By: Relevance
“…Good efficacy in DS was observed by several centers (65-66% responders and 0-6% seizure free), respectively (Laux and Blackford, 2013;Nabbout et al, 2011) and also by our group with 70% response and 10% seizure freedom (Dressler et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
“…Good efficacy in DS was observed by several centers (65-66% responders and 0-6% seizure free), respectively (Laux and Blackford, 2013;Nabbout et al, 2011) and also by our group with 70% response and 10% seizure freedom (Dressler et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
“…There is strong evidence that the KD effectively controls seizures in patients with DS (Caraballo, 2011;Caraballo et al, 2005;Kang et al, 2005;Korff et al, 2007;Laux and Blackford, 2013), especially when added to the gold standard triple combination (Nabbout et al, 2011). Further, the diet has been reported to exhibit neuroprotective effects (Dutton et al, 2011;Luan et al, 2012) and to control long lasting SE refractory to conventional AED treatment (Nabbout et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The ketogenic diet was showed to improve the seizure thresholds in mice with SCN1A mutation which is the major cause of Dravet syndrome [14]. Previous studies demonstrated a significant reduction of seizure frequency in patients with Dravet syndrome who were maintained on this diet [15,16]. Recent evidence showed that the ketones produced after MAD could reduce synaptic transmission and neuron excitability by inhibiting glutamate transport and activation of ATP-sensitive potassium channels [17].…”
Section: Discussionmentioning
confidence: 96%